Research in place: the critical role of rural health research in Canada - Stephanie Welton; Margo Wilson; Barbara Zelek; David Pontin; Grace Perez; Nelly D. Oelke; Nelly D. Oelke; Aaron Johnston; Aaron Johnston; Jill Konkin (Frontiers in Medicine)
People in rural communities often experience different access to healthcare and services, which can lead to poorer health outcomes compared to their urban counterparts. This holds true across the international context, though our focus here is on Canada. Health research plays a crucial role in identifying challenges and solutions, and we argue that research conducted in rural communities by rural researchers is essential to addressing the unique needs of a rural population. However, several barriers hinder rural research in Canada, including inadequate infrastructure, uneven resource distribution, and the absence of a national rural research network. Prioritizing rural research is vital, as it can improve workforce recruitment and retention while guiding informed healthcare decisions and policies.